Outcome Prognostication of Acute Brain Injury using the Neurological Pupil Index (ORANGE) study: protocol for a prospective, observational, multicentre, international cohort study. - Oddo, Mauro; Taccone, Fabio; Galimberti, Stefania; Rebora, Paola; Citerio, Giuseppe (BMJ Open, 2021)
INTRODUCTION: The pupillary examination is an important part of the neurological assessment, especially in the setting of acutely brain-injured patients, and pupillary abnormalities are associated with poor outcomes. Currently, the pupillary examination is based on a visual, subjective and frequently inaccurate estimation. The use of automated infrared pupillometry to measure the pupillary light reflex can precisely quantify subtle changes in pupillary functions. The study aimed to evaluate the association between abnormal pupillary function, assessed by the Neurological Pupil Index (NPi), and long-term outcomes in patients with acute brain injury (ABI). METHODS AND ANALYSIS: The Outcome Prognostication of Acute Brain Injury using the Neurological Pupil Index study is a prospective, observational study including adult patients with ABI requiring admission at the intensive care unit. We aimed to recruit at least 420 patients including those suffering from traumatic brain injury or haemorrhagic strokes, over 12 months. The primary aim was to assess the relationship between NPi and 6-month mortality or poor neurological outcome, measured by the Extended Glasgow Outcome Score (GOS-E, poor outcome=GOS-E 1-4). Supervised and unsupervised methods and latent class mixed models will be used to identify patterns of NPi trajectories and Cox and logistic model to evaluate their association with outcome. ETHICS AND DISSEMINATION: The study has been approved by the institutional review board (Comitato Etico Brianza) on 16 July 2020. Approved protocol V.4.0 dated 10 March 2020. The results of this study will be published in peer-reviewed journals and presented at conferences. TRIAL REGISTRATION NUMBER: NCT04490005.
EVALuna2:527145